Page Header Dalam mengelola Jurnal Aplikasi Teknik Sipil, jurnal ini bekerjsama dan berafiliasi dengan Forum Pendidikan Tinggi Vokasi Indonesia jabartotojabartotonatunatoto Jurnal ini terakreditasi oleh DIRJEN DIKTI No. B/1796/E5.2/KI.02.00/2020 Ha - Septiani, Rati; Supriani, Fepy; Mase, Lindung Zalbuin; Hardiansyah; Misliniyati, Rena (Jurnal Aplikasi Teknik Sipil, 2025)
School buildings are an important tool to improve the quality of education, including junior secondary schools. Efforts to improve the quality of school buildings in Ujan Mas Subdistrict, Kepahiang Regency require identification of the physical condition of school buildings. The research conducted aims to identify the condition of the building, assess the level of damage and percentage of damage to the building elements of Junior High School buildings located in Ujan Mas District, Kepahiang Regency. The method used in this research is the weighting method by analyzing the level of damage to the building elements of the Junior High School building. The results showed that the damage condition at SMP N 1 Ujan Mas was 44.57% in the category of severe damage, SMP N 2 Ujan Mas was 42.11% in the category of moderate damage and SMP N 3 Ujan Mas was 30.07% in the category of moderate damage.